Study of the Hydration Temperature Field in the Hinge Seal Layer for a Large-Volume UHPC Arch Base - Yang, Jun; Wang, Jieyun; Luo, Chao; Ding, Yaxi; Fan, Yonghui (Frontiers in Materials, 2022)
For large arch bridges, the sealing hinge layer at the arch footing is critical to the long-term performance and durability of the structure. This paper investigated the temperature distribution of the sealing hinge layer inside a large UHPC arch seat during the hydration process under natural environment, based on a design of 600-meter span reinforced concrete rigid skeleton arch bridge. A certain suggestion for the design of large volume UHPC layer was proposed through the consideration of temperature and age effects of the thermal field solid finite element analysis of early age UHPC hydration heat. The results show that: UHPC has a hydration induction period of 10 hours and reaches the peak temperature of 69°C in 20 hours. Then, the hydration heat is gradually released in 70 hours after pouring. The maximum temperature difference between the core and surface reaches 40°C. The results also show that the early temperature field and heat release rate of UHPC are affected by initial temperature. The actual heat release of some materials of UHPC components at 75 hours is equivalent to that at 300 hours, and the minimum effective age was found close to 100hour where the heat release reaches 0.25 of the total heat release. A simplified algorithm for the spatially time-varying non-linear temperature field of the UHPC sealing hinge layer under the influence of temperature and age is proposed, which provides a simple calculation method for the temperature control of UHPC arch seat during hydration process in real projects.